The Effect of Metal Concentration on the Parameters Derived from Complexometric Titrations of Trace Elements in Seawater—A Model Study - Gledhill, Martha; Gerringa, Loes J. A. (Frontiers in Marine Science, 2017)
In this study we examine the impact of dissolved metal concentrations on the parameters that are commonly determined from complexometric titrations in seawater. We use the non-ideal competitive adsorption (NICA) model within the framework of the chemical speciation program visual MINTEQ with iron as a model metal. We demonstrate that dissolved iron concentrations effect the determined parameters for a heterogeneous binding site distribution with a fixed concentration of dissolved organic carbon. The commonly used terms ‘ligand concentration’ and ‘binding constant’ are therefore dependent on metal concentration, so we adopt the terminology suggested by Town and Filella (Limnology and Oceanography, 45, 1341-1357, 2000) and use the terms ligand quotient and stability quotient here. The systematic increase in the ligand quotient with dissolved iron concentration likely contributes towards the trend of increasing ligand quotient with dissolved iron concentration observed in field studies, and makes it hard to assign an objective meaning to the parameter. We suggest that calculation of the side reaction coefficient, a parameter that describes the probability that any added metal will be complexed, could be less prone to bias and misinterpretation than calculation of conditional stability and ligand quotients. We explore the impact of experimental design on side reaction coefficients by applying different detection windows, and multiwindow and reverse titration approaches. We identify the method that results in the best estimates of side reaction coefficients over a range of iron concentrations between 0.1 and 1.5 nmol L-1. We find that single window titrations can only reliably estimate side reaction coefficients over a limited range of iron concentrations. Multiwindow titrations provided estimates of side reaction coefficients within the 99 % confidence interval of the values calculated directly from the NICA model at all iron concentrations examined here. We recommend that future reports of speciation measurements consider the potential influence of metal concentrations on the determined parameters and future studies focus on developing and applying experimental designs that improve the robustness and rigor of chemical speciation analysis in the marine environment.